2020
DOI: 10.1002/mp.14505
|View full text |Cite
|
Sign up to set email alerts
|

Bi‐objective optimization of catheter positions for high‐dose‐rate prostate brachytherapy

Abstract: Bi-objective simultaneous optimization of catheter positions and dwell times for highdose-rate (HDR) prostate brachytherapy, based directly on dose-volume indices, has shown promising results. However, optimization with the state-of-the-art evolutionary algorithm MO-RV-GOMEA so far required several hours of runtime, and resulting catheter positions were not always clinically feasible. The aim of this study is to extend the optimization model and apply GPU parallelization to achieve clinically acceptable comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…In the article by van der Meer et al., 8 Multi‐Objective Real‐Valued Gene‐pool Optimal Mixing Evolutionary Algorithm (MO‐RV‐GOMEA) is used to optimize the catheter placement and the plans together. A comparison with our original CVT (oCVT) is also performed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the article by van der Meer et al., 8 Multi‐Objective Real‐Valued Gene‐pool Optimal Mixing Evolutionary Algorithm (MO‐RV‐GOMEA) is used to optimize the catheter placement and the plans together. A comparison with our original CVT (oCVT) is also performed.…”
Section: Discussionmentioning
confidence: 99%
“…This aspect has been partially answered with the new CVT optimization, which increases the acceptance rate even for a low number of catheters. With GOMEA, 8 the optimization process for a fixed number of catheters and multiple plans takes about 5 min. In the case of CVT, a multiple numbers of catheters are optimized, and plans are immediately optimized, which take less than 40 s in total.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hybrid inverse planning optimization (HIPO), for example, is a popular option that uses stochastic simulated annealing to optimize catheter locations followed by a deterministic dose volume histogram‐based optimization of dwell times 21 . Other heuristics and linear programming‐based models for catheter selection have also been presented and shown to improve dosimetry 22–25 . In 2021, Wang et al.…”
Section: Introductionmentioning
confidence: 99%
“…21 Other heuristics and linear programming-based models for catheter selection have also been presented and shown to improve dosimetry. [22][23][24][25] In 2021, Wang et al proposed a fast-iterative shrinkage thresholding algorithm (FISTA) with a group sparsity term and adaptive heuristic group sparsity weighting to perform simultaneous dwell time optimization and catheter selection. 26 They concluded that this was an effective method for catheter selection and improved OAR sparing in the final plans over manual catheter placement.…”
Section: Introductionmentioning
confidence: 99%